Differences in the Cardiorespiratory Fitness of Employees of PT Pos Indonesia Regional IV Jakarta Based on Body Mass Index and Other Factors - Pradini, Rizkya Wida; Sudiarti, Trini; Achmad, Engkus Kusdinar (KnE Life Sciences, 2018)
Low cardiorespiratory fitness is associated with the risk of cardiovascular disease and hypertension. Cardiorespiratory fitness in workers is low. This study examined differences in cardiorespiratory fitness based on body mass index (BMI), body fat percentage, dietary intake, physical activity, smoking status, and sleep quality. The study design was cross-sectional, and it was conducted between April and May 2016 with 124 sedentary employees (66 men and 58 women) of PT Pos Indonesia Regional IV Jakarta. Cardiorespiratory fitness was measured by the YMCA (Young Men’s Christian Association) 3-min step test.Chi-square was conducted to determine differencesin the cardiorespiratory fitness status based on Body Mass Index (BMI), body fat percentage, physical activity, smoking status, and sleep quality. Independent T-test was conducted to determine the mean differences dietary intake based on cardiorespiratory fitness.The results showed that 55(44.4%) of the 124 employees had poor cardiorespiratory fitness.BMI and body fat percentage, in addition to dietary energy intake, carbohydrate intake, and iron intake, were associated with significant differences in cardiorespiratory fitness. Based on these results, employees are advised to monitor their BMI and body fat regularly, increase their levels of physical activity, and consume a nutritionally balanced diet.